Effect of Liquidity Management, Asset Management and Liability Management on Profit - Satria, Indra (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2016)
Abstract: Effect of Liquidity Management, Asset Management and Liability Management on Profit. The purpose of this research is to propose a multiple linear regression model that can be used as a profit prediction model. The research was conducted to the porcelain, ceramic and glass companies listed in Indonesian Stock Exchange for the period of 2009-2015. They had to have audited financial reports and make a profit over that period. In this research, the independent variables were Current Ratio (CR), Total Assets Turnover Ratio (TATO), and Debt Ratio (DR). These variables were used as proxy for liquidity management, asset management, and liability management. Meanwhile, Return on Assets ratio (ROA) was dependent variable used as a proxy for profit. The result showed that liquidity management, asset management and debt management have significant effect on profit.Keyword: Current Ratio, Debt Ratio, Return on Asset, Total Asset TurnoverAbstrak: Pengaruh Manajemen Likuiditas, Manajemen Aset dan Manajemen Utang Terhadap Laba. Penelitian ini bertujuan untuk mengemukakan model regresi linier berganda yang dapat digunakan sebagai model penaksir terhadap laba. Penelitian dilakukan terhadap perusahaan porselin, keramik dan gelas yang listing di BEI pada periode 2009-2015, memunyai laporan keuangan auditan dan memeroleh laba selama periode tersebut. Variabel independen dalam penelitian ini adalah Current Ratio (CR), Total Assets Turnover Ratio (TATO), dan Debt Ratio (DR). Ketiga variabel ini masing-masing digunakan sebagai proksi manajemen likuiditas, manajemen aset, dan manajemen utang. Sementara, Return on Assets Ratio (ROA) adalah variabel dependen yang digunakan sebagai proksi laba. Hasil penelitian menunjukkan bahwa manajemen likuiditas, manajemen aset dan manajemen utang berpengaruh signifikan terhadap laba.Kata kunci: Current Ratio, Debt Ratio, Return on Asset, Total Asset Turnover